Investigation on the Curvature Correction Factor of Extension Spring - Tan, P S; Akhavan Farid, Ali; Karimzadeh, Atefeh; Rahimian Koloor, Seyed Saeid; Petrů, Michal (Materials (Basel, Switzerland), 2020)
The curvature correction factor is an important parameter in the stress calculation formulation of a helical extension spring, which describes the effect of spring wire curvature on the stress increase towards its inner radius. In this study, the parameters affecting the curvature correction factor were investigated through theoretical and numerical methods. Several finite element (FE) models of an extension spring were generated to obtain the distribution of the tensile stress in the spring. In this investigation, the hook orientation and the number of coils of the extension spring showed significant effects on the curvature correction factor. These parameters were not considered in the theoretical model for the calculation of the curvature correction factor, causing a deviation between the results of the FE model and the theoretical approach. A set of equations is proposed for the curvature correction factor, which relates both the spring index and the number of coils. These equations can be applied directly to the design of extension springs with a higher safety factor.
Keywords: hook orientation; number of coils; curvature correction factor; spring index; finite element method; extension spring